Development of ultrasonic direct joining of thermoplastic to laser structured metal. (March 2016) - Yeh, Ren-Yu; Hsu, Ray-Quen
Abstract: This work reports on an improved ultrasonic welding process for the direct joining of thermoplastic and metal. A metal thin plate was structured with grid arrays on a micro-scale level by laser irradiation. A thermoplastic part was placed on the structured region, and ultrasonic welding or ultrasonic hot welding was applied. The thermoplastic was locally melted and re-solidified in the structured grooves with very low energy input due to the tiny initial contact area of the grid tips. Single lap shear specimens and boss specimens were used to study the feasibility and performance of hybrids made by this joining method. Both shear strength and normal tensile strength were affected by changes in the grid structures and welding parameters, and the experimental results show that the micro-structure geometry of the metal plate is a major factor in the joining strength. Successful welds required that process cycle times be less than 1 s. Furthermore, the mold holding the metal sheet was heated in the ultrasonic hot welding experiments, and the heated mold significantly enhanced the joint quality. Ultrasonic hot welding appears to be a fast, low cost, and reliable method to produce plastic/metal hybrid products for electronics and other industrial applications.